Методологічні засади дослідження євроінтеграційних процесів (на прикладі інтеграції Румунії до ЄС) - Мельничук, Любов Ністорівна (Історико-політичні проблеми сучасного світу, 2022)
The article is devoted to methodological principles of researching EU integration processes. The article analyzes the theoretical background of various scientific theories of European integration, research methods and their use for studying Romaniaʼs accession to the EU. The main theoretical and conceptual approaches to the study of European integration are disclosed and the specifics of the using various approaches and methods during the study of the integration process are determined. The author studied the theoretical approaches and concepts to determine the concept of «integration», the peculiarities of some scientific theories and methods concerning the EU integration associations. The author emphasizes the diversity of approaches and methods for studying European integration processes. It should be mentioned, that the foremost theoretical and methodological approaches to the European integration problems, and the degree of the given research development were systematized. Furthermore, peculiarities of European Union-Romania’s relations establishment and EU-Romania’s ties sustainable development on the assessment stage of Romania Eurointegration were disclosed. Of particular interest is EU-Romania relationship dynamics study, major problems and peculiarities of Romania-EU cooperation throughout the evaluation stage, the progress of negotiations on the accession of Romania to the EU is under study. The specific features of Romania’s European integration ratification on the implementation stages revealed the impact and outcome of Romania’s accession to the EU. Negotiations on Romania’s joining the EU demonstrated a considerable backlog state from other prospective member-states. The estimated term of its accession was 2007 because of unwillingness Romania’s membership. Romania’s accession to the EU January 1, 2007 became a dramatic step in its development. The Bucharest’s priority directions faced a challenge of problem-solving in legal system and its corruption. The key to the Romanians’ exercising all EU citizens’ fundamental rights aimed at settling these issues. Noteworthy, a thorough scrutiny of political and legal principles of Romania’s eurointegration manifests a distinct correlation of domestic and foreign factors impact on the system of their relations. European integration of Romania was and remains logical, but dissonant process. Significantly, it is for that reason Romania steadily promotes the EU-Romania interaction and considers the time has come for the first tangible results, and consequently, is worth further investigating.
Methodological Principles of Researching EU Integration Processes (The Case of Romania Joining the EU)
Keywords: Ключові слова: теорія, підхід, метод, Румунія, Європейський Союз